The Effect of tonB Gene on the Virulence of Pseudomonas plecoglossicida and the Immune Response of Epinephelus coioides - Hu, Lingfei; Zhao, Lingmin; Zhuang, Zhixia; Wang, Xiaoru; Fu, Qi; Huang, Huabin; Lin, Lili; Huang, Lixing; Qin, Yingxue; Zhang, Jiaonan; Yan, Qingpi (Frontiers in Microbiology, 2021)
Pseudomonas plecoglossicida is the causative agent of “visceral white spot disease” in cultured fish and has resulted in serious economic losses. tonB gene plays a crucial role in the uptake of nutrients from the outer membranes in Gram-negative bacteria. The previous results of our lab showed that the expression of tonB gene of P. plecoglossicida was significantly upregulated in the spleens of infected Epinephelus coioides. To explore the effect of tonB gene on the virulence of P. plecoglossicida and the immune response of E. coioides, tonB gene of P. plecoglossicida was knocked down by RNAi and the differences between the wild type strain and the tonB-RNAi strain of P. plecoglossicida were investigated. The results showed that: all of the 4 mutants of P. plecoglossicida exhibited significant decreases in mRNA of tonB gene, and the best knocked down efficiency was 94.0%; the survival rate of E. coioides infected by tonB-RNAi strain was 20% higher than of the counterpart infected by wild strain of P. plecoglossicida. Meanwhile, the E. coioides infected by tonB-RNAi strain of P. plecoglossicida carried less pathogens in the spleen and less white spots on the surface of spleen; compared with the wild type strian, the motility, chemotaxis, adhesion and biofilm formation of tonB-RNAi strain were significantly attenuated; the transcriptome data of E. coioides infected by the tonB-RNAi strain were different from the counterpart infected by wild strain of P. plecoglossicida, the antigen processing and presentation pathway and the complement and coagulation cascade pathway were the most enriched immune pathways. The results indicated that: tonB was a virulence gene of P. plecoglossicida; tonB gene was involved in the regulation of motility, chemotaxis, adhesion and biofilm formation; tonB gene affected the immune response of E. coioides to P. plecoglossicida infection.